2020
DOI: 10.1128/mbio.01930-20
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Is Restricted by Zinc Finger Antiviral Protein despite Preadaptation to the Low-CpG Environment in Humans

Abstract: Recent evidence shows that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is sensitive to interferons (IFNs). However, the most effective types of IFNs and the underlying antiviral effectors remain to be defined. Here, we show that zinc finger antiviral protein (ZAP), which preferentially targets CpG dinucleotides in viral RNA sequences, restricts SARS-CoV-2. We further demonstrate that ZAP and its cofactors KHNYN and TRIM25 are expressed in human lung cells. Type I, II, and III IFNs all strongly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
135
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(154 citation statements)
references
References 72 publications
12
135
0
Order By: Relevance
“…Our observations are compatible with the notion that cytoplasmic ZAP can bind to CpG dinucleotides to facilitate the degradation of viral transcripts. This idea, in conjunction with our observations, is corroborated by a recent study that found ZAP targets CpG to restrict SARS-CoV-2 replication in human lung cells [17]. In contrast to ZAP, APOBEC3 enzymes are mostly expressed in immune cells such as CD4 + T cells residing in tissues [22].…”
Section: Plos Onesupporting
confidence: 91%
See 3 more Smart Citations
“…Our observations are compatible with the notion that cytoplasmic ZAP can bind to CpG dinucleotides to facilitate the degradation of viral transcripts. This idea, in conjunction with our observations, is corroborated by a recent study that found ZAP targets CpG to restrict SARS-CoV-2 replication in human lung cells [17]. In contrast to ZAP, APOBEC3 enzymes are mostly expressed in immune cells such as CD4 + T cells residing in tissues [22].…”
Section: Plos Onesupporting
confidence: 91%
“…To determine the nucleotide mutation patterns over time at each viral region, each aligned sequence was grouped into one of six time ranges, and the time range within each group was PLOS ONE determined as the number of days passed since the reference strain (Wuhan-Hu-1, 2019- [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Note that the number of days between time intervals is unequal, because strains were grouped based on roughly equal sample size and not by equal number of days.…”
Section: Determining the Temporal And Geographical Patterns Of Snps Imentioning
confidence: 99%
See 2 more Smart Citations
“…Solving the crystal structure of ZAP in complex with CG-rich RNA revealed that ZAP has a CGdinucleotide specific binding pocket and binds to ss nucleic acids (150,151). ZAP preference for CG-rich substrates could explain in part why many RNA viruses infecting mammals and other vertebrates, such as IAV and SARS-CoV-2, exhibit CG suppression (152)(153)(154)(155). ZAP can even sense CG dinucleotides within individual RNA transcripts of DNA viruses, as in the case of human cytomegalovirus (156).…”
Section: Zapmentioning
confidence: 99%